Financing of innovative development in the construction industry of Ukraine - Halunka О. D. (Ways to Improve Construction Efficiency, 2018)
This article is devoted to determining the relevance of the study of innovative development in the construction industry of Ukraine and determining its priority areas. These scientists are known to have been researching the issues of innovative development in Ukraine as a whole and in the construction industry for a long time. One of the important issues is the current state of innovation development, which directly depends on the funding of research and development and the cost of their implementation from various sources in Ukraine and in the construction industry during 2013-2018. In the first place financially influential on innovation development is the state budget, scientific works are also significantly financed at the expense of enterprises of Ukraine and foreign countries, recently there has been an increase in the population’s own investment.